Black Women in the Rijksmuseum’s Sixteenth- and Seventeenth-Century Collection - Stephanie Archangel; Maria Holtrop (The Rijksmuseum Bulletin, 2024)
The few studies of the depiction of Black people in Western art have focused primarily on the rendering of Black men. This article discusses the depictions of Black women in the Rijksmuseum’s collection, specifically in the sixteenth and seventeenth centuries, from the moment that Europeans and Africans met until about 1660, when representations became increasingly stereotyped. Black women in this period are depicted in a number of genres. The illustrations in travel journals and separate drawn records are concerned primarily with the differences in status between local inhabitants: the more clothes they wore, the higher their status. Yet the texts accompanying these depictions link nakedness to barbarity and lewdness. That nudity was retained as the way to represent allegorical Africa, in the form of a nearly naked Black female surrounded by wild animals, as was also prescribed in the iconographic manual by Cesare Ripa. When she was positioned in the company of the other continents, she was assigned a subordinate role as being less civilized and ripe for the taking. The Black woman also has a minor part as the allegory of Night or Darkness. In Biblical scenes the Black female is an individual character in some cases while in others she is a bystander, like white onlookers. There are no examples known of Black women who commissioned portraits themselves. There are, however, tronies that were intended to represent African facial features and a black skin, sometimes including an ‘exotic’ costume. Two etchings of Black females in everyday clothing might depict members of the Black communities that had settled in Antwerp, like they did in Amsterdam. Such illustrations made from life are too few in number, however, to express with subtlety the image of the Black woman countering the predominant image of her as an ‘exotic’, sexual apparition. It is possible that this analysis can be adapted on the basis of research into depictions in other – non-Northern-European – collections.